Hubungan Antara Motivasi Bidan DenganKepatuhan Pemberian Informed ConsentPada Pelayanan Keluarga Berencana(Kb) Di Kecamatan Grogol - Kusumawati, Intan, Purwanti, SKM, M.Kes, Kusuma Estu W, SKM, M.Kes (2016)
Results IDHS (Indonesian Demographic and Health Survey), CPR (Contraseptive Prevalence Rate) rose by only 0.5%, from 57.4% (2007) to 57.9% (2012). This is due to high drop out rate of participation in family planning (20% -27%), and the low use of long-term methods (25.1%). Midwives as the provider is responsible for documenting the informed consent of obstetrics one KB. Giving informed consent KB can significantly prevent the drop out of contraceptive use. This study aims to determine the relationship between motivation midwife to compliance with the provision of informed consent to service of Family Planning (KB) in Grogol. This research method using observational analytic design with cross sectional approach. The population of this research is all midwives working in the area of Grogol 61 midwives. Selection of the sample with simple random sampling as much as 38 midwives. The statistical test using chi square. The results showed that there was a relationship between motivation midwife to compliance with the provision of informed consent to service of Family Planning (KB), (p-value = 0.022).